Development and Validation of a Small Single-domain Antibody That Effectively Inhibits Matrix Metalloproteinase 8 - Demeestere, Delphine (Mol Ther, 2016)
A detrimental role for matrix metalloproteinase 8 (MMP8) has been identified in several pathological conditions, e.g., lethal hepatitis and the systemic inflammatory response syndrome. Since matrix MMP8-deficient mice are protected in the above-mentioned diseases, specific MMP8 inhibitors could be of clinical value. However, targeting a specific matrix metalloproteinase remains challenging due to the strong structural homology of matrix metalloproteinases, which form a family of 25 members in mammals. Single-domain antibodies, called nanobodies, offer a range of possibilities toward therapy since they are easy to generate, express, produce, and modify, e.g., by linkage to nanobodies directed against other target molecules. Hence, we generated small MMP8-binding nanobodies, and established a proof-of-principle for developing nanobodies that inhibit matrix metalloproteinase activity. Also, we demonstrated for the first time the possibility of expressing nanobodies systemically by in vivo electroporation of the muscle and its relevance as a potential therapy in inflammatory diseases.